Dementia With Lew Body: Impacts of Surgery. (February 2016) - Pervin, Farzana; Edwards, Carolyn; Lippa, Carol F.
Patients who have dementia with Lewy bodies (DLB) and undergo surgery may develop aggravated postoperative cognitive dysfunction or postoperative delirium. Many patients with DLB respond poorly to surgery and anesthesia, and their conditions may worsen if they have other medical complications along with dementia. They may also face high risk of prolonged hospital stay, increased medical problems and/or mortality, causing significant physical, psychosocial, and financial burdens on individuals, family members, and society. Anesthesia, pain medications, old age, and surgery-related stresses are usually held responsible for the complications; however, the exact causes are still not fully understood. Literature on surgery-related complications for patients with DLB appears to be inadequate, and hence the topic merits detailed and systematic research. This article reviews postoperative complications and various surgery-related risk factors for DLB in light of other dementias such as Alzheimer's disease, as their neuropathologic features overlap with those of DLB.